A critical readability and quality analysis of internet‐based patient information on neck dissections. Issue 1 (26th April 2022) - Grose, Elysia M.; Kim, Joo Hyun; Philteos, Justine; Levin, Marc; Lee, Jong Wook; Monteiro, Eric A.
Abstract: Objective: Patients are increasingly turning to the Internet as a source of healthcare information. Given that neck dissection is a common procedure within the field of Otolaryngology ‐ Head and Neck Surgery, the aim of this study was to evaluate the quality and readability of online patient education materials on neck dissection. Methods: A Google search was performed using the term "neck dissection." The first 10 pages of a Google search using the term "neck dissection" were analyzed. The DISCERN instrument was used to assess quality of information. Readability was calculated using the Flesch‐Reading Ease, Flesch‐Kincaid Grade Level, Gunning‐Fog Index, Coleman‐Liau Index, and Simple Measure of Gobbledygook Index. Results: Thirty‐one online patient education materials were included. Fifty‐five percent ( n  = 17) of results originated from academic institutions or hospitals. The mean Flesch‐Reading Ease score was 61.2 ± 11.9. Fifty‐two percent ( n  = 16) of patient education materials had Flesch‐Reading Ease scores above the recommended score of 65. The average reading grade level was 10.5 ± 2.1. The average total DISCERN score was 43.6 ± 10.1. Only 26% of patient education materials (PEMs) had DISCERN scores corresponding to a "good quality" rating. There was a significant positive correlation between DISCERN scores and both Flesch‐Reading Ease scores and average reading grade level. Conclusions: The majority of patient education materials were written above the recommended sixth‐grade reading level and the quality of online information pertaining to neck dissections was found to be suboptimal. This research highlights the need for patient education materials regarding neck dissection that are high quality and easily understandable by patients.